A new species of Hydara (Hemiptera: Coreidae: Coreinae: Hydarini) from Madagascar - Brailovsky, Harry (Zootaxa, 2006)
Hydara kmenti new species, collected in Madagascar is described. The relationships with Hydara tenuicornis (Westwood) and Hydara nigrofasciata Garcia Varela are discussed. The adult dorsal habitus, and drawings of pronotum, male genital capsule, and female genital plates are included, as is a key to the Madacascar Hydarini.